Integrated photovoltaic storage joint smoothing strategy based on simultaneous perturbation stochastic approximation algorithm - Yujing, He; Jie, Chen; Xueqin, Tian; Yafei, Wang (Frontiers in Energy Research, 2023)
In order to realize the real-time control of photovoltaic power generation smoothly connected to the grid under the condition that the energy storage equipment can operate safely, a control strategy combining the simultaneous perturbation stochastic approximation (SPSA) algorithm with rule control is designed. Firstly, the photovoltaic data are processed to extract the data characteristics of the power ramp, and then the grid-connected reference power is obtained through SPSA algorithm. Secondly, considering the state of charge (SOC) of energy storage equipment and the safe operating power range of hydrogen storage equipment, 24 hybrid energy storage power allocation rules are formulated by using the rule control method. Finally, according to the sampling data of every 10 s interval in typical day, the simulation is carried out on MATLAB/simulink platform. The results show that, compared with the first-order low-pass filtering algorithm and recursive fuzzy neural network (RFNN) algorithm, the SPSA algorithm has stronger smoothing ability, and the rule control can also complete the allocation according to the characteristics of the hybrid storage device while ensuring its normal operation.